Number of opioid overdoses and depression as a predictor of suicidal thoughts. (1st July 2021) - Brown, Lily A.; Denis, Cecile M.; Leon, Anthony; Blank, Michael B.; Douglas, Steven D.; Morales, Knashawn H.; Crits-Christoph, Paul F.; Metzger, David S.; Evans, Dwight L.
Highlights: Opioid users completed medical/psychiatric interviews with a mobile research team. Number of prior overdoses and depression were associated with suicidal thoughts. Opioid users with 3 or more overdoses or depression always be screened for suicide. All opiate users should be regularly screened for overdoses, depression and suicidal thoughts. Abstract: Background: Opioid use disorders are associated with increased risk of suicide thoughts, attempts, and death. We explored key variables from two theories of the development of suicidal thoughts and attempts (the interpersonal and three-step theories of suicide) to understand possible mechanisms underlying the association between opioid use and suicide risk. We hypothesized that interpersonal connections, variables reflecting psychological and physical pain, and variables that reduce fear of death (prior overdoses and risk-taking behaviors) would be associated with increased risk of thoughts of suicide. Methods: Participants ( N  = 141) were opioid users recruited from an epicenter of the opioid crisis in Philadelphia using a mobile research center and completed an interview to assess substance use, depression, medical comorbidities, and suicidal thoughts among other variables. Results: Univariate analyses showed that prior history of overdose, diagnosis of depression, older age, homelessness, and interpersonal connection were each associated with increased likelihood of endorsing thoughts of death/suicide. Multivariable analyses revealed prior history of overdose and depression were the variables most strongly associated with risk for thoughts of suicide. Conclusions: Consistent with two theories of the development of suicidal thoughts and attempts, exposure to variables that reduce fear of death (e.g., overdoses) were associated with suicidal thoughts. In contrast, other risk-taking behaviors, medical comorbidities, and substance use were not key predictors of suicidal thoughts in this sample. Implications for targeted risk assessment among clinicians are discussed.